Studi Perilaku Harian Rusa Timor (Cervus timorensis) di Kawasan Savana Bekol Taman Nasional Baluran Situbondo - Bayuda Luqman Alfarisi; Amaliya Nailatul Musyarrafah (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2023)
Baluran National Park is a conservation area with a climate and geography that supports the formation of dry savanna on the island of Java, so it is also known as